2017
DOI: 10.1111/cbdd.12818
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized calix[4]arenes as potential therapeutic agents

Abstract: Calixarenes, composed of phenolic units linked by methylene bridges at the 2,6-positions, represent a versatile class of macrocyclic compounds in supramolecular chemistry that can host small molecules or ions in their well-defined hydrophobic cavities. In recent years, it has been recognized that this class of compounds has the potential to serve as platform for the design of biological active compounds. Therefore, the calixarenes functionalized with different pharmacophoric groups have been synthesized as tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 89 publications
(134 reference statements)
0
29
0
Order By: Relevance
“…Calixarenes derived from base‐catalyzed condensation of 4‐ tert ‐butylphenol/formaldehyde have found widespread application as building blocks for the design and synthesis of functional materials in host–guest chemistry . Such calixarenes exist as multiple conformers, affording further tailoring of their properties.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Calixarenes derived from base‐catalyzed condensation of 4‐ tert ‐butylphenol/formaldehyde have found widespread application as building blocks for the design and synthesis of functional materials in host–guest chemistry . Such calixarenes exist as multiple conformers, affording further tailoring of their properties.…”
Section: Figurementioning
confidence: 99%
“…We find that 3/3 + C is ar emarkable receptor for NO + /NO, with unprecedented binding efficacy.T he availability of precise experimental structures of this calixarene derivative and its NO complex,o btained by X-ray crystallography,i sc ritically important both for developing novel functional NO biosensors, and understanding the role of stacked aromaticd onors in efficient NO binding, which may have relevance to biologicalN O transport.Calixarenes derived from base-catalyzedc ondensation of 4tert-butylphenol/formaldehyde have found widespread application as buildingb locks for the design and synthesis of functional materials in host-guest chemistry. [1][2][3][4][5][6][7] Such calixarenes exist as multiple conformers,a ffording further tailoring of their properties. It has been shown that, upon its activation via 1Àe À oxidation, the conformationally mobile p-tert-butylcalix[4]arene-OMe (1)b inds nitric oxide (NO) with nanomolar efficiency (K > 5 10 8 )l eading to the formation of the [1,N O] + complex.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of macrocycles as scaffolds is highlighted by Naseer and co‐workers with a review on therapeutic potential of calix[4]arenes. Calix[4]arenes are well known for their well‐defined central cavity and host–guest properties, but the potential of these structures as molecular scaffolds for biologically active molecules is less well appreciated.…”
Section: Comparison Of Lipinski Ro5 With Ppi Inhibitors and Macrocyclmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Among the various molecular scaffolds that have been used for this purpose, one of the mostn otable is calix [4]arene, ac lass of macrocycles that has been widely employeda sb uildingb locks and molecular platforms in supramolecular chemistry. [11,[15][16][17][18][19][20][21][22][23][24][25][26] Calix [4]arenes are conformationally mobile moleculest hat have four conformers,t hat is, 1,3-alternate, 1,2-alternate, cone, and partial cone, with different cavity sizes. Therefore, calix [4]arenes have many potential applicationsi ns upramolecular host-guest chemistry and molecular sensing,s uch as the sensing of NO.…”
Section: Introductionmentioning
confidence: 99%